PENGARUH KECERDASAN EMOSIONAL DAN SIKAP KERJA TERHADAP PENGAMBILAN KEPUTUSAN - Subandijo Subandijo (JURNAL MITRA MANAJEMEN, 2012)
ABSTRACTThe obyective of this research is to study the effect of emotional intelligence, job attitudeson individual decision making. The research was conducted at the Suryadarma University inJakarta. It was using causal study method. The samples of this research were 90 personel of theSuryadarma University that selected randomly.The research findings are: (1) there is a direct effect of emotional on individual decisionmaking (2) there is a direct effect of job attitudes on individual decision making.Based on these findings, could be concluded that individual decision making is affected byemotional intelligence and job attitudes. And the emotional intelligence is the most dominant thateffect the decision making. On the other word, the higher emotional intelligence effects moredirectly on the individual decision makin.gTherefore, the emotional intelligence and job attitudes should be taken into consideration indetermining individual decision making.